2018
DOI: 10.1063/1.5011400
|View full text |Cite
|
Sign up to set email alerts
|

Negative stiffness honeycombs as tunable elastic metamaterials

Abstract: Acoustic and elastic metamaterials are media with a subwavelength structure that behave as effective materials displaying atypical effective dynamic properties. These material systems are of interest because the design of their sub-wavelength structure allows for direct control of macroscopic wave dispersion. One major design limitation of most metamaterial structures is that the dynamic response cannot be altered once the microstructure is manufactured. However, the ability to modify wave propagation in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…Another aspect that this work has highlighted is the quasi‐zero stiffness shown by the auxetic sandwich beams under large bending deformations. Negative stiffness has been considered both for controllable large deformations at reduced actuation force, and large damping/energy dissipation, even with auxetic characteristic . Zero stiffness is, however, another type of anomalous mechanical system with interesting characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that this work has highlighted is the quasi‐zero stiffness shown by the auxetic sandwich beams under large bending deformations. Negative stiffness has been considered both for controllable large deformations at reduced actuation force, and large damping/energy dissipation, even with auxetic characteristic . Zero stiffness is, however, another type of anomalous mechanical system with interesting characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…These metamaterials have all shown excellent mechanical properties, such as rate-independent mechanism, recoverability from large elastic deformation, tremendous freedom of performance-oriented design and extraordinary energy-absorption capacity, especially for dynamic loads. Works done by Goldsberry et al [ 37 ] and Nadkarni et al [ 38 ] have also shown rich dynamic response with distinct regimes of wave propagation and the ability to modify wave propagation in the metamaterial with an external stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the active metamaterials with smart materials, tunable metamaterials can also be realized by passive means. [13][14][15][16][17][18] For example, by imposing mechanical deformation, a given bandgap can be adaptively tuned or switched on and off with buckling elastic beams. 14 With large deformations of curved beams subjected to prestrain in a honeycomb structure, tunable dispersion properties of elastic metamaterials can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…14 With large deformations of curved beams subjected to prestrain in a honeycomb structure, tunable dispersion properties of elastic metamaterials can be achieved. 17 By varying the applied temperature to change the temperaturedependent moduli of the constituent materials, metamaterialbased bandgaps can be made tunable. 18 For the buckling-based or deformation-based tunable metamaterials, substantially flexible materials/structures have to be implemented in design and fabrication.…”
Section: Introductionmentioning
confidence: 99%